Antibacterial Activity of Hoya Diversifolia Ethanolic Leaves Extract - Ab-Rahim, Nurhidayah; Ismail, Wan Ismahanisa; Fikri Roslan, Muhammad Nabil; Hafiz Mail, Mohd; Che Lamin, Roz Azinur; Ismail, Salmah (Oriental Scientific Publishing Company, 2019)
The rapid emergence of resistance bacteria toward various antibiotics may associate with higher medical cost and increase mortality rate. Hoya diversifolia was used to cure skin diseases and alleviate rheumatism pain. The aim of this study is to evaluate in vitro antibacterial properties of H. diversifolia ethanolicleaves extract against several Gram positive and Gram negative bacteria. The antibacterial study was determined based on pattern of inhibition zones using disc diffusion assay and also minimal inhibitory concentration (MIC). It is shown that the extract can inhibit the growth of methicillin-resistant Staphylococcus aureus,Escherichia coliandBacillus cereus.The lowest MIC values of extract were 25 mg/mL for MRSA and E. coli as well as 100 mg/mL for B. cereus at 24 and 48 hours of incubation period. The plant had potential to act as antibacterial agent that can be applied in pharmaceutical and cosmetic fields. © 2019 Oriental Scientific Publishing Company. All rights reserved.